Human Rights for The Elderly Group in Indonesia: Elderly in The Era of Covid 19 - Anang Darwisyi Baidhowi (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The 1945 Constitution essentially guarantees that every citizen in national development in all aspects of life